Crack growth in a naturally corroded bridge steel. Issue 7 (22nd December 2016) - Ali, K; Peng, D; Jones, R; Singh, R R K; Zhao, X L; McMillan, A J; Berto, F
Abstract: This paper summarises the findings of an international collaborative programme that focuses on the problem of the growth of cracks that arise from natural corrosion in bridge steels. The experimental data presented in this paper confirm that the bridge steel da/dN versus Δ K relationship is similar to that seen by the high‐strength aerospace steels D6ac and 4340. It is then shown that the methodology developed to predict the growth of small naturally occurring cracks in aerospace materials can also be used to compute the growth of cracks that arise because of natural corrosion in bridge steels.